Neuropharmacological Potential of Gastrodia elata Blume and Its Components. (12th October 2015) - Jang, Jung-Hee; Son, Yeonghoon; Kang, Seong Soo; Bae, Chun-Sik; Kim, Jong-Choon; Kim, Sung-Ho; Shin, Taekyun; Moon, Changjong
Abstract : Research has been conducted in various fields in an attempt to develop new therapeutic agents for incurable neurodegenerative diseases. Gastrodia elata Blume (GE), a traditional herbal medicine, has been used in neurological disorders as an anticonvulsant, analgesic, and sedative medication. Several neurodegenerative models are characterized by oxidative stress and inflammation in the brain, which lead to cell death via multiple extracellular and intracellular signaling pathways. The blockade of certain signaling cascades may represent a compensatory therapy for injured brain tissue. Antioxidative and anti-inflammatory compounds isolated from natural resources have been investigated, as have various synthetic chemicals. Specifically, GE rhizome extract and its components have been shown to protect neuronal cells and recover brain function in various preclinical brain injury models by inhibiting oxidative stress and inflammatory responses. The present review discusses the neuroprotective potential of GE and its components and the related mechanisms; we also provide possible preventive and therapeutic strategies for neurodegenerative disorders using herbal resources.